The Effectiveness of Assertiveness Skills Training on Emotional Self-Awareness and Interpersonal Difficulties among Male High School Students - Arastehfard, Mehdi; Mohammadzadeh, Rajabali; Asnafy , Zahra (KMAN Counseling & Psychology Nexus, 2026)
The present study was conducted to investigate the effectiveness of assertiveness skills training on emotional self-awareness and interpersonal difficulties among male high school students in Babol County. This study employed a quasi-experimental design using a pretest–posttest control group framework. The statistical population consisted of male students enrolled in the second cycle of secondary education (high school) in Babol County. A total of 40 students were randomly assigned to either an experimental group (n = 20) or a control group (n = 20). Participants completed the Emotional Self-Awareness Questionnaire developed by Grant et al. and the Interpersonal Difficulties Questionnaire developed by Engels (2005). The experimental group received assertiveness skills training, while the control group received no intervention. At the end of the intervention, both groups completed the questionnaires again as a posttest measure. The data were analyzed using multivariate and univariate analyses of covariance (MANCOVA and ANCOVA). The findings indicated that assertiveness skills training had a statistically significant effect on both emotional self-awareness and interpersonal difficulties. Based on the eta-squared values, the strongest effect was observed for interpersonal difficulties, accounting for approximately 58% of the variance, followed by emotional self-awareness, accounting for approximately 44% of the variance. The results suggest that assertiveness skills training increased emotional self-awareness and reduced interpersonal difficulties among male high school students in Babol County.